Ocular drug delivery from contact lenses: mimetizing the hydrodynamic conditions of the eye - Pimenta, Andreia (2018)
Poster presented at the 4th Congress on Innovation in Drug Delivery Site-Specific Drug Delivery (IDD2016). Antibes-Juan-les-Pins, France, 25-28 September 2016